Development and Management News Site www.rumahkartini.com - Nurul Laelatul Latifah; Primada Qurrota Ayun, S.I.Kom, MA (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2017)
Starting from human resources that competent in Rumah Kartini Community capable of managing the website www.rumahkartini.com regularly and in accordance with the rules of journalism, the author wants to develop human resources and managing the website www.rumahkartini.com under the Rumah Kartini continued and to be able to manage well in accordance with the community's vision and mission. In the paper the author this field served as a Reporter and Editor. The reporter in charge of finding and writing the news. The editor in charge of news texts edited before uploading into the website and selecting the news that will be uploaded. The results of the development of human resources in this community they are able to continue manage website with good information and renew frequently. The results of the management of www.rumahkartini.com for one month is uploading the article as much as 31 and the number of visitors 4,334 as much as the minimum target of 1500 visitors. And able to manage 4 sections namely Tempo Doeloe, Discovery, Kulineran and Event.